Pancasila as a Paradigm of Public Transportation Development - Achmad Khiyarul Wahdi; Nurani Saida Latifah; Masduki Asbari (Journal of Information Systems and Management (JISMA), 2022)
This article discusses the economic conception of Pancasila which is based on strategic values ​​in the application of the five precepts formulated by the Founding Fathers of the Nation. The method in this research is Library Research, the study process is in the form of library research, either in the form of books, notes, or reports of previous research results. The results of the study in this research are the Pancasila Economy has the spirit of divinity, humanity, national unity, democracy and social justice. The conclusion of this study is that Pancasila Economy is present in the form of a Transportation Company as a paradigm that aims to realize the development of the Indonesian economy and realize the welfare of the Indonesian people.